Global Warming, Technology Transfer and Trade in Carbon Energy: Challenge or Threat? - Georg Müller-Fürstenberger; Gunter Stephan (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2012)
Is it possible to combat global climate change through North-to-South technology transfer even without a global climate treaty? Or do carbon leakage and the rebound effect imply that it is possible to take advantage of technological improvements under the umbrella of a global arrangement only? For answering these questions a world with full international cooperation is compared with a world, where countries act non-cooperatively. More precisely, in case of non-cooperation two cases are discussed. The first one is called Kyoto-plus and the second one labeled Kyoto-reversed. Kyoto-plus means that the North decides: (1) to unilaterally reduce its domestic greenhouse gas emissions and (2), to transfer technological knowledge to the South. If Kyoto-reversed is considered, the North decides on transferring technology while the South commits itself to reduce emissions. Rebound and leakage effects hinder a sustainable and welfare improving solution of the climate problem.
Keywords: 330